Accelerometer-derived physical activity and sedentary behaviors in individuals with newly diagnosed type 2 diabetes: A cross-sectional study from the Danish nationwide DD2 cohort - Domazet, Sidsel L.; Tarp, Jakob; Thomsen, Reimar W.; Højlund, Kurt; Stidsen, Jacob V.; Brønd, Jan C.; Grøntved, Anders; Nielsen, Jens Steen (Frontiers in Sports and Active Living, 2023)
Introduction Habitual physical activity behaviors of individuals with new-onset type 2 diabetes are largely unknown. We aimed to investigate accelerometer-derived physical activity behaviors in individuals with newly diagnosed type 2 diabetes. We also examined sociodemographic and health-related correlates of a high-risk physical activity profile. Methods This cross-sectional study used data from 768 participants enrolled in an intervention study nested within the Danish Centre for Strategic Research in Type 2 diabetes (DD2) cohort. Physical activity was assessed by 24-h dual monitor accelerometry. Prevalence ratios of having a high-risk physical activity profile were estimated using Poisson regression adjusted for age and sex. Results Study participants spent on average 9.7 (25th and 75th percentiles, 8.3; 11.1) hours/day sitting, walked for 1.1 (0.8; 1.6) hours/day and accumulated 4,000 (2,521; 5,864) steps/day. Still, 62% met the recommendations for physical activity. Characteristics associated with a high-risk physical activity profile (observed in 24.5% of participants) included older age, higher body mass index (BMI), unemployment, retirement, comorbidities, and current smoking. Hence, participants aged 60–69, 70–79 and 80+ years had prevalence ratios of 2.12 (95% CI 1.31; 3.42), 1.99 (1.18; 3.34) and 3.09 (1.42; 6.75) for a high-risk activity profile, respectively, versus participants <50 years. BMI values of 30–39 and 40+ were associated with 1.83 (1.06; 3.15) and 3.38 (1.88; 6.05) higher prevalence ratios compared to normal-weight. Unemployment or retirement was associated with 1.62 (1.09; 2.41) and 2.15 (1.37; 3.39) times higher prevalence ratios, compared to individuals in the working force. Having a Charlson Comorbidity Index score of 1–2 or 3+ was associated with 1.36 (1.03–1.79) and 1.90 (1.27–1.84) higher prevalence ratios, while current smoking was associated with a prevalence ratio of 1.72 (1.25; 2.35) compared to never smokers. Conclusion This study shows that 62% of individuals with newly diagnosed type 2 diabetes met the recommendations for physical activity. Still, the majority of participants were also highly sedentary and accumulated very few daily steps, emphasizing the need for focusing on both increasing physical activity and reducing sedentary behaviors in the prevention of diabetes-related complications. Individuals with a high-risk physical activity profile were characterized by more obesity, socioeconomic inequalities, advanced age and comorbidities. Trial registration number: NCT02015130.